Characterization of patients with severe trauma in an Intensive Care Unit - Carlos Herrera-Cartaya; Javier Alejandro Bermúdez-Ruiz; José Vladimir Brunet-Liste; Amalia Inés Luna-Capote; Heidy Rego-Avila (Universidad Médica Pinareña, 2020)
Introduction: severe trauma has a great impact on both health and economy in present-day society, with great incidence worldwide and in Cuba.